(untitled) (Applied Biological Research, 2011)
The present investigation was aimed to study the haemato-biochemical profile in grazing goats fed with the herbal extract of Hygrophila spinosa alone and in combination with concentrate supplement. The herbal treatment improved the haematological profile irrespective of concentrate supplementation in goats. Herbal treatment and concentrate supplementation also improved serum iron and copper concentration.